EVALUATION OF THE ANTIOXYDANT ACTIVITY OF THE ROSMARINUS OFFICINALIS EXTRACTS (Sciences & Technologie. C, Biotechnologies, 2012)
This work aims at evaluating the antioxydant activity taking count the content phenolics of the leave’s rosemary extracts (EBr, EAcOEt and En-BuOH), by the means of two methods: the β-carotene bleaching method and the DPPH assay. The analysis by HPLC revealed the presence of rutin and the catechin in the rosemary extracts. The results of β -Carotene-linoleic acid assay have showed an inhibiting activity of oxidation of the linoleic acid for the whole of the extracts, the latter significantly remains lower than that of positive control BHT (P